P1743IMPORTANCE OF KIDNEY ALLOGRAFT REJECTİON IN BK VIRUS NEPHROPATHY. (6th June 2020) - Demir, Erol; Kayaş, Kamil; Erel, Cansu; Caparali, Bilge; Ozler, Tuba Elif; Dirim, Ahmet Burak; Catikkas, Nezahat Muge; Guller, Nurana; Safak, Seda; Ucar, Ali Riza; Oto, Ozgur Akin; Yazici, Halil; et al.
Abstract: Background and Aims: Allograft rejection following BK virus nephropathy (BKVN) is an important cause of allograft loss in kidney transplant recipients. However, the effect of rejection type on allograft survival in patients with BKVN has not been described previously. This study aimed to investigate the relationship between allograft rejection type and graft survival in patients with BKVN. Method: We retrospectively analyzed the data of 159 kidney transplant recipients diagnosed BKVN and followed-up in our center between January 2009 and December 2019. BKVN was diagnosed by persistent viremia of more than 10000 copies/mL for four weeks or allograft biopsy. Vascular, obstructive or other non-parenchymal etiologies for allograft dysfunction were excluded. All patients were investigated for the presence of anti-HLA antibody at 6 and 12 months after BKVN diagnosis. Luminex solid-phase assay was used to investigate Class I and Class II PRA and MFI values greater than 1000 were accepted as positive. Allograft biopsy was performed in patients with progressive graft dysfunction or the presence of donor-specific antibodies (DSA) and analyzed according to the Banff Classification. The primary outcomes were defined as allograft loss or the allograft dysfunction which defined as was doubling serum creatinine levels. Results: Patients were followed-up median 70 (IQR 13-198) months after kidney transplantation. Demographic data and clinical characteristics are provided in the table. 28 kidney transplant recipients suffered from allograft rejection after BKVN. Median rejection time to rejection after BKVN was 9 (IQR 5-164) months. 3 patients (18, 8%) in the AMR group and 1 patient (8, 3%) in the TCMR group experienced graft loss during follow-up. The mean serum creatinine levels at the last clinical visit were significantly higher in the AMR group compared to the TCMR group (1, 9±0, 8 vs 1, 3±1, 2 mg/dl; p=0, 002). In multivariate analysis, AMR was an independent risk factor for allograft dysfunction (HR, 1, 735; 95% CI 1, 060 to 2, 839; p=0, 028). Conclusion: The occurrence of AMR after BKVN is an important indicator of allograft dysfunction compared to TCMR. DSA screening should be routinely used in this group for early diagnosis and treatment of AMR.